Peasant Wisdom for the Nurturing of the Potato in the Aimara Communities of Altiplano, Puno - Inquilla Mamani, Juan (2021)
The purpose of this article is to offer an analysis of the ancestral knowledge of the Aimara about the nurturing of the potato crop, and to identify the different forms of conversations with the agroecosystemic signs. The methodological perspective is ethnographic and qualitative, based on face to face interview technique and participant observation. The results of the research show that, in the Andean communities of Puno, the breeding of the potato is closely linked to climate behavior, therefore, the conversations with the agroecosystemic signs, is constant in response to the different stages of the agricultural cycle.